Multidisciplinary Practice Variations of Anti-Thrombotic Strategies for Free Tissue Transfers. Issue 4 (November 2022) - Huynh, Minh N. Q.; Bhagirath, Vinai; Gupta, Michael; Avram, Ronen; Cheung, Kevin
Background: Venous thrombosis, the leading cause of free flap failure, may have devastating consequences. Many anti-thrombotic agents and protocols have been described for prophylaxis and treatment of venous thrombosis in free flaps.Methods: National surveys were distributed to microsurgeons (of both Plastics and ENT training) and hematology and thrombosis specialists. Data were collected on routine screening practices, perceived risk factors for flap failure, and pre-, intra-, and post-operative anti-thrombotic strategies.Results: There were 722 surveys distributed with 132 (18%) respondents, consisting of 102 surgeons and 30 hematologists. Sixty-five surgeons and 9 hematologists routinely performed or managed patients with free flaps. The top 3 perceived risk factors for flap failure according to surgeons were medical co-morbidities, past arterial thrombosis, and thrombophilia. Hematologists, however, reported diabetes, smoking, and medical co-morbidities as the most important risk factors. Fifty-four percent of physicians routinely used unfractionated heparin (UFH) or low-molecular-weight heparin (LMWH) as a preoperative agent. Surgeons routinely flushed the flap with heparin (37%), used UFH IV (6%), or both (8%) intra-operatively. Surgeons used a range of post-operative agents such as UFH, LMWH, aspirin, and dextran while hematologists preferred LMWH. There was variation of management strategies if flap thrombosis occurred. Different strategies consisted of changing recipient vessels, UFH IV, flushing the flap, adding post-operative agents, or a combination of strategies.Conclusions: There are diverse practice variations in anti-thrombotic strategies for free tissue transfers and a difference in perceived risk factors for flap failure that may affect patient management.